Calculation of CaCO3 Solubility (Precipitability) in Natural Waters - Qian, H.; Zhang, X.D.; Li, P.Y. (Asian Journal of Chemistry, 2011)
It is an important issue to calculate the CaCO3 solubility (precipitability) in natural waters in karst geochemistry. This paper pointed out some serious problems in the existing methods dealing with this issue and put forward a new method to calculate the CaCO3 solubility (precipitability) in natural waters. This new method is based on the calculation of CaCO3 saturation index and takes the changes of pH values, activity coefficients and concentration changes of species into account and these factors are studied in open and closed systems, respectively. The results showed that if the above-mentioned changes were ignored, there would be significant errors in the calculated results.